Tafsir Ayat ‘Tidak Ada Paksaan dalam Agama’ Perspektif Al Harari - Asyhari (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The term 'religious freedom' is controversial among religious communities, particularly among Muslims. Both supporters and opponents within the Muslim community present arguments based on scriptural (Qur'an and Hadith) and rational reasoning. Those supporting religious freedom often cite verses like